Reduction of graphene oxide in ethanol solution by gamma irradiation for preparing reduced graphene oxide material with water desalination - Pham , Thi Thu Hong; Nguyen , Thanh Duoc; Nguyen , Thi Ly; Chu , Nhut Khanh; Cao , Van Chung; Doan, Binh (Nuclear Science and Technology, 2019)
Reduction of graphene oxide (GO) for preparing the reduced graphene oxide (rGO) by γ–ray irradiation was investigated. GO was dispersed in the ethanol solution with the GO concentration of 1 mg/ml, then irradiated with γ–ray in presence of oxygen at dose range of 0 – 100 kGy for preparation of rGO product. The characteristic properties of GO and rGO were determined by UV-Vis spectroscopy, X–ray diffraction (XRD), Transmission Electron Microscopy (TEM), contact angle measurement and test of water desalination. The result showed that water desalination efficiency of rGO was about 46 – 48%.